Storytelling sebagai Teknik Persuasif: Studi pada Gaya Komunikasi Kreator TikTok dalam Iklan Digital - Ayuningtyas, Fitria; Surbakti, Grace Christine (Tuturlogi: Journal of Southeast Asian Communication, 2025)
Storytelling marketing is currently growing on the social media platform TikTok. To craft compelling and engaging storytelling, an appropriate communication style is essential. This study aims to identify and understand the Communication Style of Content Creators in Delivering Storytelling in TikTok Advertisement Content, specifically analyzing the communication style of Sena Farid, using Norton's communication style theory as a conceptual framework. This research uses a qualitative method, with subjects selected through purposive sampling. The study employs virtual ethnography analysis, which includes four levels of analysis: Media Space, Media Archive, Media Object, and Experiential Stories. To ensure the validity of the data, source triangulation was used. The study's results revealed several key findings regarding the communication style of content creators in delivering storytelling on TikTok ads, particularly on Sena Farid's account. The research found that Sena Farid's communication styles tend to fall under the categories of Impression-Leaving, Animated Expressive, Dramatic, and Friendly. Furthermore, the study identified Sena Farid's descriptions of communication style in storytelling, which include comforting visuals, warm narration, and a clear purpose, serving as references for other content creators to develop their communication styles.